Platinum–copper single atom alloy catalysts with high performance towards glycerol hydrogenolysis - Xi Zhang (Nature Portfolio, 2019)
Selective hydrogenolysis of biomass glycerol to propanediol is a promising route for the production of high-value chemicals but remains a challenge. Here, the authors find a PtCu single atom alloy catalyst exhibits remarkably boosted performance with a turnover frequency value of 2.6 × 103 molglycerol·molPtCu–SAA −1·h−1.